Archived government correspondence reveals extreme arsenic pollution of local waterbodies from gold mining at Yellowknife, NT prior to environmental regulation - Michael J. Palmer; John Chételat; Heather E. Jamieson; Christine McClelland; Seamus Daly (FACETS)
The Yellowknife area was one of the most productive and profitable gold districts in Canadian history. The early years of operation were associated with large releases of mining waste to local water bodies that have resulted in an enduring environmental legacy in the region. Here, we compile, for the first time, archival information on the scale of impact to local waterbodies during the highest environmental emissions (1949–1956). More than 800 measurements of arsenic (As) concentrations from local waterbodies, ponded surface water, and domestic water sources were extracted from archived government documents during this period. The compilation of these data revealed extreme and widespread arsenic contamination of local waterbodies from mining operations with concentrations up to 47 000 µg L−1 As. The archived correspondence included documentation of public health effects revealing that local mining emissions were a public health risk during this period. Comparison of the archived water quality records with contemporary data for the same lakes indicated widespread reductions of lake water arsenic concentrations across the region over half a century. These data provide evidence of the extent of historical environmental impacts of mining on Indigenous territory and of government and industry failure to stop emissions when faced with evidence that local mines were causing environmental pollution and risks to public health. By bringing these data to light, it is hoped that this information will support reconciliation efforts between the federal and territorial governments and local Indigenous Peoples.